A high thermal conductivity graphene composite material for heat dissipation of VR equipment and preparation method thereof

By adjusting the ratio of reduced graphene oxide powder/paraffin and hollow mesoporous silica in graphene composite materials, more thermal conduction channels and frameworks are established, and the phase change process of paraffin absorbs heat, solving the problems of heat dissipation and surface temperature control of VR equipment is achieved, and efficient heat dissipation and mechanical strength are improved.

CN119161693BActive Publication Date: 2025-03-21ZHEJIANG AIFA ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411687610.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-21
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

VR equipment generates a lot of heat during operation. If it cannot effectively dissipate heat, it will not only affect the performance of the equipment, but also cause the components to overheat and shorten the service life. At the same time, existing highly thermally conductive graphene composites may cause the surface temperature of VR equipment to rise too quickly, increasing the heat risk of user skin contact.

Method used

By adjusting the ratio of reduced graphene oxide powder/paraffin to hollow mesoporous silica, the heat storage capacity of graphene composite materials is improved and the skeleton of composite materials is built, more thermal conductivity channels are established, and heat transfer is effectively transferred. Paraffin absorbs a large amount of heat through the phase change process to prevent the equipment surface temperature from rising sharply, while hollow mesoporous silica improves the heat dissipation effect and mechanical strength of the material.

Benefits of technology

While effectively dissipating heat, it can avoid the surface temperature of VR equipment from rising too quickly, reduce the risk of users being exposed to heat, and improve the mechanical strength and structural stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161693B_ABST
    Figure CN119161693B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of composite materials, and provides a high thermal conductivity graphene composite material for heat dissipation of VR equipment and a preparation method thereof, wherein the high thermal conductivity graphene composite material comprises reduced graphene oxide powder / paraffin, hydrazine hydrate solution, hollow mesoporous silica, polyvinyl alcohol, epoxy resin, polyvinyl pyrrolidone and deionized water; the present invention introduces paraffin into graphene, which can absorb a large amount of latent heat during the phase change process, and will not cause the surface temperature of the VR equipment to rise rapidly, and releases the latent heat absorbed before when the temperature drops, thereby preventing the phenomenon of uneven hot and cold; subsequently, hollow mesoporous silica is added, and its mesoporous structure can not only establish more heat conduction channels in the composite material, but also form a microscopic skeleton in the material, thereby enhancing the thermal conductivity and overall strength of the composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite materials and relates to a high thermal conductivity graphene composite material for heat dissipation of VR equipment and a preparation method thereof. Background Art

[0002] As the performance of virtual reality (VR) devices continues to improve, the power consumption and heat generated by VR devices are also increasing. Heat dissipation has become one of the important bottlenecks restricting its further development. VR device components generate a lot of heat during operation. If the heat cannot be effectively dissipated, it will not only affect the performance of the device, but also cause the components to overheat and shorten their service life.

[0003] In order to solve these problems, high thermal conductivity composite materials have gradually become a research hotspot. Graphene is considered to be an ideal choice for manufacturing high thermal conductivity composite materials due to its excellent thermal conductivity and lightweight properties. Although high thermal conductivity graphene composite materials can effectively reduce the internal temperature of VR devices, they still face a key problem in practical applications. VR devices are usually in direct contact with the user's face and head. If the heat dissipation material is not designed properly, the heat will cause the surface temperature of the VR device to rise too quickly and be transferred to the user's skin through the heat conduction path, causing discomfort or even the risk of burns. How to effectively dissipate heat while preventing the surface temperature of VR devices from rising too quickly has become a technical problem that needs to be solved in the current VR device heat dissipation design. Summary of the invention

[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a high thermal conductivity graphene composite material for heat dissipation of VR equipment and a preparation method thereof. By adjusting the ratio of reduced graphene oxide powder / paraffin wax and hollow mesoporous silica, the heat storage capacity of the graphene composite material is improved and the skeleton of the composite material is constructed, more thermal conduction channels are established, and heat can be effectively transferred; paraffin wax absorbs a large amount of heat through the phase change process to prevent the surface temperature of the equipment from rising too quickly; hollow mesoporous silica will also improve the heat dissipation effect and mechanical strength of the graphene composite material, thereby meeting the needs of actual production.

[0005] To achieve this object, the present invention adopts the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment, the preparation method comprising:

[0007] Step S1, dispersing 0.5-1.3 parts by weight of graphene oxide in 200 parts by weight of deionized water, stirring and ultrasonicating at a first stirring speed to obtain a suspension, adding 3-6 parts by weight of a hydrazine hydrate solution to the suspension, reacting at a first temperature, and stirring at a first stirring speed, washing and centrifuging after the reaction is completed, and freeze-drying to obtain reduced graphene oxide powder;

[0008] Step S2, immersing 0.5-1 parts by weight of reduced graphene oxide powder in 20-30 parts by weight of paraffin wax and maintaining the mixture at a second temperature under a vacuum state, cooling the mixture to room temperature after the reaction is completed and removing the paraffin wax on the surface of the reduced graphene oxide powder to obtain reduced graphene oxide powder / paraffin wax;

[0009] Step S3, 2-3 parts by weight of reduced graphene oxide powder / paraffin, 15-20 parts by weight of deionized water, 5-7 parts by weight of hollow mesoporous silica and 5-8 parts by weight of polyvinyl alcohol are sequentially added to 60-70 parts by weight of epoxy resin, and stirred at a second stirring speed, and then 5-10 parts by weight of polyvinyl pyrrolidone are added, and mixed at a second stirring speed to obtain a mixed solution A;

[0010] Step S4, pouring the mixed solution A into a mold, and vacuum drying it to obtain a high thermal conductivity graphene composite material for heat dissipation of VR equipment.

[0011] The role of adding paraffin is:

[0012] (1) Paraffin is a typical phase change material with a low melting point (40°C~65°C). During the phase change process, it can change from solid to liquid, and can absorb and store a large amount of thermal energy without causing a sharp rise in the surface temperature of the device. This latent heat storage capacity is very effective for temperature control and thermal management of electronic equipment. When the temperature drops, paraffin will change from liquid back to solid and release the latent heat previously absorbed. This process can help evenly distribute the heat inside the material and prevent uneven cooling. The thermal buffering effect brought about by the phase change of paraffin helps to reduce the thermal stress caused by temperature fluctuations during operation of the equipment and protect electronic components from damage.

[0013] (2) Paraffin can be physically adsorbed and coated on the surface of graphene to form a composite material. In this composite structure, the flow of paraffin can be restricted between graphene sheets. Graphene can wrap and fix paraffin by constructing a three-dimensional network structure. This structure not only enhances the mechanical stability of paraffin, but also provides a large number of thermal conduction channels, thereby improving the thermal conductivity of the entire composite material.

[0014] The role of adding hollow mesoporous silica is:

[0015] (1) Hollow mesoporous silica has a large specific surface area and mesoporous structure, which helps to improve the overall thermal conductivity of the composite material. Although the thermal conductivity of silica itself is low, its mesoporous structure can establish more thermal conduction channels in the composite material. When used in conjunction with graphene, it can effectively transfer heat. The hollow mesoporous structure can help to more evenly distribute and conduct heat inside the material, prevent local heat accumulation, and avoid local overheating of the material;

[0016] (2) Hollow mesoporous silica can be used as a carrier for phase change materials (such as paraffin). Its mesoporous structure can adsorb and encapsulate paraffin, prevent paraffin from leaking during the phase change process, and maintain the overall structural stability of the material. The structure of hollow mesoporous silica can increase the contact area between paraffin and thermal conductive materials (such as graphene), improve the heat transfer efficiency during the phase change process, and enable the material to absorb and release heat more quickly.

[0017] (3) The addition of hollow mesoporous silica can significantly improve the mechanical strength and toughness of the composite material. It can form a microscopic support skeleton in the material, enhance the overall structural stability of the composite material, and prevent the material from breaking or deforming due to temperature changes or external forces during use. Since hollow mesoporous silica has a low density, its addition can enhance the structural properties and thermal conductivity of the material without significantly increasing the weight of the material.

[0018] As a preferred technical solution of the present invention, in step S1, the graphene oxide is 0.5-1.3 parts by weight, for example, it can be 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts, 1.1 parts, 1.2 parts or 1.3 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0019] In some optional examples, the first stirring speed is 300-400 rpm, for example, it can be 300 rpm, 310 rpm, 320 rpm, 330 rpm, 340 rpm, 350 rpm, 360 rpm, 370 rpm, 380 rpm, 390 rpm or 400 rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0020] In some optional instances, the ultrasound time is 30-50 min, for example, it can be 30 min, 32 min, 34 min, 36 min, 38 min, 40 min, 42 min, 44 min, 46 min, 48 min or 50 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0021] In some optional examples, the hydrazine hydrate solution is 3-6 parts by weight, for example, it can be 3 parts, 3.3 parts, 3.6 parts, 3.9 parts, 4.2 parts, 4.5 parts, 4.8 parts, 5.1 parts, 5.4 parts, 5.7 parts or 6 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] In some optional instances, the first temperature is 65-75°C, for example, it can be 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 71°C, 72°C, 73°C, 74°C or 75°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0023] In some optional examples, the reaction time is 12-14 h, for example, it can be 12 h, 12.2 h, 12.4 h, 12.6 h, 12.8 h, 13.0 h, 13.2 h, 13.4 h, 13.6 h, 13.8 h or 14 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] In some optional embodiments, the freeze-drying time is 10-12 h, for example, it can be 10 h, 10.2 h, 10.4 h, 10.6 h, 10.8 h, 11.0 h, 11.2 h, 11.4 h, 11.6 h, 11.8 h or 12 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] As a preferred technical solution of the present invention, in step S2, the reduced graphene oxide powder is 0.5-1 parts by weight, for example, it can be 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts or 1 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] In some optional examples, the paraffin is 20-30 parts by weight, for example, it can be 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts or 30 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0027] In some optional instances, the second temperature is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0028] In some optional instances, the immersion time is 30-40 min, for example, it can be 30 min, 31 min, 32 min, 33 min, 34 min, 35 min, 36 min, 37 min, 38 min, 39 min or 40 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0029] As a preferred technical solution of the present invention, in step S3, the reduced graphene oxide powder / paraffin is 2-3 parts by weight, for example, it can be 2 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.7 parts, 2.8 parts, 2.9 parts or 3 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0030] In some optional examples, the deionized water is 15-20 parts by weight, for example, it can be 15 parts, 15.5 parts, 16.0 parts, 16.5 parts, 17.0 parts, 17.5 parts, 18.0 parts, 18.5 parts, 19.0 parts, 19.5 parts or 20 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0031] In some optional examples, the hollow mesoporous silica is 5-7 parts by weight, for example, it can be 5 parts, 5.2 parts, 5.4 parts, 5.6 parts, 5.8 parts, 6.0 parts, 6.2 parts, 6.4 parts, 6.6 parts, 6.8 parts or 7 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0032] In some optional examples, the polyvinyl alcohol is 5-8 parts by weight, for example, it can be 5.0 parts, 5.3 parts, 5.6 parts, 5.9 parts, 6.2 parts, 6.5 parts, 6.8 parts, 7.1 parts, 7.4 parts, 7.7 parts or 8.0 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0033] In some optional examples, the epoxy resin is 60-70 parts by weight, for example, it can be 60 parts, 61 parts, 62 parts, 63 parts, 64 parts, 65 parts, 66 parts, 67 parts, 68 parts, 69 parts or 70 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0034] In some optional examples, the second stirring speed is 350-450rpm, for example, it can be 350rpm, 360rpm, 370rpm, 380rpm, 390rpm, 400rpm, 410rpm, 420rpm, 430rpm, 440rpm or 450rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0035] In some optional examples, the polyvinyl pyrrolidone is 5-10 parts by weight, for example, it can be 5 parts, 5.5 parts, 6.0 parts, 6.5 parts, 7.0 parts, 7.5 parts, 8.0 parts, 8.5 parts, 9.0 parts, 9.5 parts or 10 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0036] In some optional examples, the stirring time is 40-60 min, for example, it can be 40 min, 42 min, 44 min, 46 min, 48 min, 50 min, 52 min, 54 min, 56 min, 58 min or 60 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0037] As a preferred technical solution of the present invention, in step S4, the drying temperature is 55-65°C, for example, it can be 55°C, 56°C, 57°C, 58°C, 59°C, 60°C, 61°C, 62°C, 63°C, 64°C or 65°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0038] In some optional examples, the drying time is 4-6 hours, for example, it can be 4h, 4.2h, 4.4h, 4.6h, 4.8h, 5.0h, 5.2h, 5.4h, 5.6h, 5.8h or 6.0h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0039] The hollow mesoporous silica preparation method comprises:

[0040] Step I, dissolving 2-3 parts by weight of hexadecyltrimethylammonium bromide in an ethanol aqueous solution, then adding 4-5 parts by weight of triethanolamine to the ethanol aqueous solution, and stirring and dissolving at a third speed to obtain a mixed solution B;

[0041] Step II, heating the mixed solution B to a third temperature, adding 6-8 parts by weight of tetraethoxysilane at a fourth stirring speed and refluxing at the third temperature, and obtaining a preformed product by centrifugation after the reaction is completed;

[0042] Step III, adding the preformed product into a hydrochloric acid / ethanol solution, ultrasonically treating to remove the unreacted solvent and forming a hollow structure, and finally washing by centrifugation with ethanol and deionized water three times, and freeze-drying to obtain hollow mesoporous silica.

[0043] Hexadecyltrimethylammonium bromide is a cationic surfactant that spontaneously forms a micelle structure when dissolved in an ethanol-water solution. Triethanolamine is a weakly alkaline triol that interacts with hexadecyltrimethylammonium bromide in an ethanol-water solution after being added. Triethanolamine can act as a buffer around the micelles to stabilize the pH value of the solution. It also helps to maintain the stability of the micelles and provides a template for the subsequent formation of silica. Tetraethoxysilane will undergo a hydrolysis reaction in water and ethanol solutions, and the generated silanol molecules will further undergo a condensation reaction to form a silicon-oxygen bond (Si-O-Si), thereby forming a mesh structure of silica. Hydrochloric acid can effectively destroy the micelle structure of hexadecyltrimethylammonium bromide, exposing the silica shell wrapped therein to form a hollow structure. It can also dissolve and remove unreacted silicates to further purify silica particles.

[0044] As a preferred technical solution of the present invention, in step I, the hexadecyltrimethylammonium bromide is 2-3 parts by weight, for example, it can be 2 parts, 2.1 parts, 2.2 parts, 2.3 parts, 2.4 parts, 2.5 parts, 2.6 parts, 2.7 parts, 2.8 parts, 2.9 parts or 3 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0045] In some optional examples, the triethanolamine is 4-5 parts by weight, for example, it can be 4 parts, 4.1 parts, 4.2 parts, 4.3 parts, 4.4 parts, 4.5 parts, 4.6 parts, 4.7 parts, 4.8 parts, 4.9 parts or 5 parts, but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0046] In some optional examples, the third stirring speed is 300-400rpm, for example, it can be 300rpm, 310rpm, 320rpm, 330rpm, 340rpm, 350rpm, 360rpm, 370rpm, 380rpm, 390rpm or 400rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] In some optional examples, the stirring time at the third speed is 20-30 min, for example, it can be 20 min, 21 min, 22 min, 23 min, 24 min, 25 min, 26 min, 27 min, 28 min, 29 min or 30 min, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0048] As a preferred technical solution of the present invention, in step II, the third temperature is 80-90°C, for example, it can be 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0049] In some optional examples, the fourth stirring speed is 350-450rpm, for example, it can be 350rpm, 360rpm, 370rpm, 380rpm, 390rpm, 400rpm, 410rpm, 420rpm, 430rpm, 440rpm or 450rpm, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0050] In some optional examples, the tetraethoxysilane is 6-8 parts by weight, for example, it can be 6 parts, 6.2 parts, 6.4 parts, 6.6 parts, 6.8 parts, 7.0 parts, 7.2 parts, 7.4 parts, 7.6 parts, 7.8 parts or 8 parts, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0051] In some optional instances, the reflux time is 2-3 h, for example, 2 h, 2.1 h, 2.2 h, 2.3 h, 2.4 h, 2.5 h, 2.6 h, 2.7 h, 2.8 h, 2.9 h or 3 h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0052] As a preferred technical solution of the present invention, in step III, the ultrasonic power of the ultrasonic treatment is 500-800 W, for example, it can be 500 W, 530 W, 560 W, 590 W, 620 W, 650 W, 680 W, 710 W, 740 W, 770 W or 800 W, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0053] In some optional embodiments, in step III, the ultrasonic time is 4-6h, for example, it can be 4h, 4.2h, 4.4h, 4.6h, 4.8h, 5.0h, 5.2h, 5.4h, 5.6h, 5.8h or 6h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0054] In some optional embodiments, in step III, the drying time is 10-12 hours, for example, it can be 10 hours, 10.2 hours, 10.4 hours, 10.6 hours, 10.8 hours, 11.0 hours, 11.2 hours, 11.4 hours, 11.6 hours, 11.8 hours or 12 hours, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0055] In a second aspect, the present invention provides a high thermal conductivity graphene composite material for heat dissipation of VR devices obtained by using the method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR devices described in the first aspect.

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] (1) Paraffin is a typical phase change material that can absorb a large amount of latent heat. It absorbs and stores a large amount of thermal energy during the phase change process without causing a sharp rise in the material temperature. This latent heat storage capacity is very effective for temperature control and thermal management of electronic equipment. When the temperature drops, paraffin will solidify from liquid to solid and release the latent heat previously absorbed. This process can help evenly distribute the heat inside the material and prevent uneven cooling. At the same time, graphene can wrap and fix paraffin by constructing a three-dimensional network structure. This structure not only enhances the mechanical stability of paraffin, but also provides a large number of thermal conduction channels, thereby improving the thermal conductivity of the entire composite material.

[0058] (2) Hollow mesoporous silica has a large specific surface area and mesoporous structure. The mesoporous structure can establish more thermal conduction channels in the composite material. When used in combination with graphene, it helps to improve the overall thermal conductivity of the composite material. The addition of hollow mesoporous silica can significantly improve the mechanical strength and toughness of the composite material. It can form a microscopic support skeleton in the material, enhance the overall structural stability of the composite material, and prevent the material from breaking or deforming due to temperature changes or external forces during use. Since hollow mesoporous silica has a low density, its addition can enhance the structural performance and thermal conductivity of the material without significantly increasing the weight of the material. The present invention can effectively dissipate heat while preventing the surface temperature of the VR device from rising too quickly. BRIEF DESCRIPTION OF THE DRAWINGS

[0059] Figure 1 A flow chart of a method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment provided in Examples 1 to 8 of the present invention;

[0060] Figure 2 This is a SEM image of reduced graphene oxide prepared in Example 1 of the present invention;

[0061] Figure 3This is a SEM image of the reduced graphene oxide powder / paraffin prepared in Example 1 of the present invention;

[0062] Figure 4 This is a SEM image of the hollow mesoporous silica prepared in Example 1 of the present invention;

[0063] Figure 5 This is a TEM image of the hollow mesoporous silica prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0064] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.

[0065] The chemical reagents used in the examples and comparative examples of the present invention are all commercially available products, and their brands, specifications and manufacturer information are as follows:

[0066] Graphene oxide, purity ≥98%, Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.;

[0067] Hydrazine hydrate, purity ≥98%, Henan Province Xinxiang Zhongyuan Organic Chemical Co., Ltd.;

[0068] Paraffin wax, purity ≥99%, Wuhan Dinglitai Chemical Co., Ltd.;

[0069] Polyvinyl alcohol, alcoholysis degree <95%, Shandong Quantai Chemical Technology Co., Ltd.;

[0070] Epoxy resin, volatile matter ≤ 0.3%, Shandong Deyuan Epoxy Technology Co., Ltd.;

[0071] Polyvinyl pyrrolidone, solid content ≥95%, Shanghai Vitone Material Technology Co., Ltd.;

[0072] Hexadecyltrimethylammonium bromide, purity ≥98%, Shandong Xirui Chemical Co., Ltd.;

[0073] Triethanolamine, purity ≥85%, Henan Annuo Chemical Technology Co., Ltd.;

[0074] Tetraethoxysilane, content ≥99%, Jiangxi Kerui New Materials Co., Ltd.;

[0075] Hydrochloric acid, mass fraction is 37wt.%, Suzhou Jiading Chemical Technology Co., Ltd.

[0076] Other raw materials can be purchased from the market.

[0077] Example 1

[0078] This embodiment provides a method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0079] (1) Step I, dissolving 2.6 g of hexadecyltrimethylammonium bromide in 150 mL of ethanol aqueous solution, adding 4.2 g of triethanolamine to the ethanol aqueous solution, and stirring at 360 rpm for 25 min to obtain a mixed solution B;

[0080] Step II, heating the mixed solution B to 84°C, adding 7.1 g of tetraethoxysilane at 400 rpm and refluxing at 84°C for 2.2 h, and obtaining a preformed product by centrifugation after the reaction is completed;

[0081] Step III, the preformed product was added to 200 mL of hydrochloric acid / ethanol solution, ultrasonically treated for 4 h to remove the unreacted solvent and form a hollow structure, and finally centrifuged and washed three times with ethanol and deionized water, and freeze-dried for 11.2 h to obtain hollow mesoporous silica.

[0082] (2) Step S1, dispersing 0.9 g of graphene oxide in 200 g of deionized water, stirring and ultrasonicating at 350 rpm for 45 min to obtain a suspension, adding 4.4 g of hydrazine hydrate solution to the suspension, reacting at 69° C. for 12.8 h, and maintaining stirring at 350 rpm. After the reaction is completed, washing and centrifuging, and freeze-drying for 11.4 h to obtain reduced graphene oxide powder;

[0083] Step S2, immersing 0.62 g of reduced graphene oxide powder in 26 g of paraffin wax and maintaining the mixture at 85° C. for 35 min under vacuum, cooling the mixture to room temperature after the reaction is completed and removing the paraffin wax on the surface of the reduced graphene oxide powder to obtain reduced graphene oxide powder / paraffin wax;

[0084] Step S3, 2.6 g of reduced graphene oxide powder / paraffin, 17 g of deionized water, 6.3 g of hollow mesoporous silica and 7.3 g of polyvinyl alcohol are added to 65 g of epoxy resin in sequence, and stirred at 420 rpm, and then 8.1 g of polyvinyl pyrrolidone is added, and the mixture is stirred at 420 rpm for 50 min to obtain a mixed solution A;

[0085] Step S4, pouring the mixed solution A into a mold, and drying it at 59° C. in a vacuum oven for 5.6 h to obtain a high thermal conductivity graphene composite material for heat dissipation of VR equipment.

[0086] Figure 2 This is the SEM image of reduced graphene oxide. Figure 3 The SEM image of reduced graphene oxide powder / paraffin shows a very obvious layered structure. Figure 4 This is the SEM picture of hollow mesoporous silica. Figure 5 TEM image of hollow mesoporous silica.

[0087] Example 2

[0088] This embodiment provides a method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0089] (1) Step I, dissolving 2.3 g of hexadecyltrimethylammonium bromide in 150 mL of ethanol aqueous solution, adding 4.7 g of triethanolamine to the ethanol aqueous solution, and stirring at 330 rpm for 28 min to obtain a mixed solution B;

[0090] Step II, heating the mixed solution B to 87°C, adding 6.9 g of tetraethoxysilane at 400 rpm and refluxing at 87°C for 2.5 h, and obtaining a preformed product by centrifugation after the reaction is completed;

[0091] Step III, the preformed product was added to 200 mL of hydrochloric acid / ethanol solution, ultrasonically treated for 5.2 h to remove the unreacted solvent and form a hollow structure, and finally centrifuged and washed three times with ethanol and deionized water, and freeze-dried for 10.6 h to obtain hollow mesoporous silica.

[0092] (2) Step S1, 0.7 g of graphene oxide was dispersed in 200 g of deionized water, and ultrasonically stirred at 330 rpm for 40 min to obtain a suspension, 3.8 g of hydrazine hydrate solution was added to the suspension, and the suspension was reacted at 71° C. for 11.8 h, and stirred at 330 rpm. After the reaction, the suspension was washed and centrifuged, and freeze-dried for 10.8 h to obtain reduced graphene oxide powder;

[0093] Step S2, immersing 0.78 g of reduced graphene oxide powder in 22 g of paraffin wax and maintaining the mixture at 82° C. for 37 min under vacuum, cooling the mixture to room temperature after the reaction is completed and removing the paraffin wax on the surface of the reduced graphene oxide powder to obtain reduced graphene oxide powder / paraffin wax;

[0094] Step S3, 2.1 g of reduced graphene oxide powder / paraffin, 18 g of deionized water, 5.9 g of hollow mesoporous silica and 6.1 g of polyvinyl alcohol are sequentially added to 66 g of epoxy resin, and stirred at 380 rpm, and then 5.4 g of polyvinyl pyrrolidone is added, and the mixture is mixed and stirred at 380 rpm for 44 min to obtain a mixed solution A;

[0095] Step S4, pouring the mixed solution A into a mold, and drying it at 62° C. in a vacuum oven for 4.6 h to obtain a high thermal conductivity graphene composite material for heat dissipation of VR equipment.

[0096] Example 3

[0097] This embodiment provides a method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0098] (1) Step I, dissolving 2 g of hexadecyltrimethylammonium bromide in 150 mL of ethanol aqueous solution, adding 4.1 g of triethanolamine to the ethanol aqueous solution, and stirring at 380 rpm for 24 min to obtain a mixed solution B;

[0099] Step II, heating the mixed solution B to 82°C, adding 7.9 g of tetraethoxysilane at 420 rpm and refluxing at 82°C for 2.3 h, and obtaining a preformed product by centrifugation after the reaction is completed;

[0100] Step III, the preformed product was added to 200 mL of hydrochloric acid / ethanol solution, ultrasonically treated for 4.2 h to remove the unreacted solvent and form a hollow structure, and finally centrifugally washed three times with ethanol and deionized water, and freeze-dried for 11.6 h to obtain hollow mesoporous silica.

[0101] (2) Step S1, dispersing 1.0 g of graphene oxide in 200 g of deionized water, stirring and ultrasonicating at 390 rpm for 45 min to obtain a suspension, adding 4.2 g of hydrazine hydrate solution to the suspension, reacting at 66° C. for 13.8 h, and stirring at 390 rpm. After the reaction, washing and centrifuging, and freeze-drying for 10.4 h to obtain reduced graphene oxide powder;

[0102] Step S2, immersing 0.59 g of reduced graphene oxide powder in 20 g of paraffin wax and maintaining the mixture at 87° C. for 33 min under vacuum, cooling the mixture to room temperature after the reaction is completed and removing the paraffin wax on the surface of the reduced graphene oxide powder to obtain reduced graphene oxide powder / paraffin wax;

[0103] Step S3, 2.7 g of reduced graphene oxide powder / paraffin, 17 g of deionized water, 6.3 g of hollow mesoporous silica and 7.1 g of polyvinyl alcohol are added to 60 g of epoxy resin in sequence, and stirred at 410 rpm, and then 7.9 g of polyvinyl pyrrolidone is added, and the mixture is mixed and stirred at 410 rpm for 54 min to obtain a mixed solution A;

[0104] Step S4, pouring the mixed solution A into a mold, and drying it at 58° C. in a vacuum oven for 5.8 h to obtain a high thermal conductivity graphene composite material for heat dissipation of VR equipment.

[0105] Example 4

[0106] This embodiment provides a method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0107] (1) Step I, dissolving 3 g of hexadecyltrimethylammonium bromide in 150 mL of ethanol aqueous solution, adding 4.9 g of triethanolamine to the ethanol aqueous solution, and stirring at 310 rpm for 22 min to obtain a mixed solution B;

[0108] Step II, heating the mixed solution B to 90°C, adding 7.5 g of tetraethoxysilane at 440 rpm and refluxing at 90°C for 2 h, and obtaining a preformed product by centrifugation after the reaction is completed;

[0109] Step III, the preformed product was added to 200 mL of hydrochloric acid / ethanol solution, ultrasonically treated for 6 h to remove the unreacted solvent and form a hollow structure, and finally centrifugally washed three times with ethanol and deionized water, and freeze-dried for 11.1 h to obtain hollow mesoporous silica.

[0110] (2) Step S1, dispersing 1.3 g of graphene oxide in 200 g of deionized water, stirring and ultrasonicating at 300 rpm for 50 min to obtain a suspension, adding 3.2 g of hydrazine hydrate solution to the suspension, reacting at 74° C. for 12 h, and stirring at 300 rpm. After the reaction is completed, washing and centrifugation are performed, and freeze-drying is performed for 11.9 h to obtain reduced graphene oxide powder;

[0111] Step S2, immersing 0.89 g of reduced graphene oxide powder in 30 g of paraffin wax and maintaining the mixture at 80° C. for 40 min under vacuum, cooling the mixture to room temperature after the reaction is completed and removing the paraffin wax on the surface of the reduced graphene oxide powder to obtain reduced graphene oxide powder / paraffin wax;

[0112] Step S3, 3 g of reduced graphene oxide powder / paraffin, 19 g of deionized water, 5.1 g of hollow mesoporous silica and 6.9 g of polyvinyl alcohol are added to 70 g of epoxy resin in sequence, and stirred at 370 rpm, and then 8.3 g of polyvinyl pyrrolidone is added, and the mixture is stirred at 370 rpm for 60 min to obtain a mixed solution A;

[0113] Step S4, pouring the mixed solution A into a mold, and drying it at 65° C. in a vacuum oven for 4 h to obtain a high thermal conductivity graphene composite material for heat dissipation of VR equipment.

[0114] Example 5

[0115] This embodiment provides a method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0116] (1) Step I, dissolving 2.5 g of hexadecyltrimethylammonium bromide in 150 mL of ethanol aqueous solution, adding 4.4 g of triethanolamine to the ethanol aqueous solution, and stirring at 350 rpm for 21 min to obtain a mixed solution B;

[0117] Step II, heating the mixed solution B to 82°C, adding 7.5 g of tetraethoxysilane at 450 rpm and refluxing at 82°C for 2.7 h, and obtaining a preformed product by centrifugation after the reaction is completed;

[0118] Step III, the preformed product was added to 200 mL of hydrochloric acid / ethanol solution, ultrasonically treated for 5.5 h to remove the unreacted solvent and form a hollow structure, and finally centrifuged and washed three times with ethanol and deionized water, and freeze-dried for 10.6 h to obtain hollow mesoporous silica.

[0119] (2) Step S1, dispersing 0.8 g of graphene oxide in 200 g of deionized water, stirring and ultrasonicating at 300 rpm for 42 min to obtain a suspension, adding 5.8 g of hydrazine hydrate solution to the suspension, reacting at 70° C. for 13.4 h, and stirring at 370 rpm. After the reaction, washing and centrifuging, and freeze-drying for 10.9 h to obtain reduced graphene oxide powder;

[0120] Step S2, immersing 0.62 g of reduced graphene oxide powder in 25 g of paraffin wax and maintaining the mixture at 83° C. for 36 min under vacuum, cooling the mixture to room temperature after the reaction is completed and removing the paraffin wax on the surface of the reduced graphene oxide powder to obtain reduced graphene oxide powder / paraffin wax;

[0121] Step S3, 2.2 g of reduced graphene oxide powder / paraffin, 18 g of deionized water, 6.3 g of hollow mesoporous silica and 7.1 g of polyvinyl alcohol are added to 66 g of epoxy resin in sequence, and stirred at 410 rpm, and then 6.2 g of polyvinyl pyrrolidone is added, and the mixture is mixed and stirred at 410 rpm for 48 min to obtain a mixed solution A;

[0122] Step S4, pouring the mixed solution A into a mold, and drying it at 61° C. in a vacuum oven for 5.2 h to obtain a high thermal conductivity graphene composite material for heat dissipation of VR equipment.

[0123] Example 6

[0124] This embodiment provides a method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0125] (1) Step I, dissolving 2.2 g of hexadecyltrimethylammonium bromide in 150 mL of ethanol aqueous solution, adding 4.1 g of triethanolamine to the ethanol aqueous solution, and stirring at 320 rpm for 27 min to obtain a mixed solution B;

[0126] Step II, heating the mixed solution B to 83°C, adding 7.5 g of tetraethoxysilane at 370 rpm and refluxing at 83°C for 2.1 h, and obtaining a preformed product by centrifugation after the reaction is completed;

[0127] Step III, the preformed product was added to 200 mL of hydrochloric acid / ethanol solution, ultrasonically treated for 4.2 h to remove the unreacted solvent and form a hollow structure, and finally centrifuged and washed three times with ethanol and deionized water, and freeze-dried for 11.3 h to obtain hollow mesoporous silica.

[0128] (2) Step S1, 0.5 g of graphene oxide was dispersed in 200 g of deionized water, and ultrasonically stirred at 380 rpm for 38 min to obtain a suspension, 3.2 g of hydrazine hydrate solution was added to the suspension, and the suspension was reacted at 66 ° C for 12.9 h, and stirred at 380 rpm. After the reaction, the suspension was washed and centrifuged, and freeze-dried for 11.1 h to obtain reduced graphene oxide powder;

[0129] Step S2, immersing 0.82 g of reduced graphene oxide powder in 23 g of paraffin wax and maintaining the mixture at 85° C. for 32 min under vacuum, cooling the mixture to room temperature after the reaction is completed and removing the paraffin wax on the surface of the reduced graphene oxide powder to obtain reduced graphene oxide powder / paraffin wax;

[0130] Step S3, 2.7 g of reduced graphene oxide powder / paraffin, 17 g of deionized water, 5.7 g of hollow mesoporous silica and 6.7 g of polyvinyl alcohol are added to 63 g of epoxy resin in sequence, and stirred at 360 rpm, and then 8.4 g of polyvinyl pyrrolidone is added, and the mixture is mixed and stirred at 360 rpm for 55 min to obtain a mixed solution A;

[0131] Step S4, pouring the mixed solution A into a mold, and drying it at 57° C. in a vacuum oven for 4.2 h to obtain a high thermal conductivity graphene composite material for heat dissipation of VR equipment.

[0132] Example 7

[0133] This embodiment provides a method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0134] (1) Step I, dissolving 2.1 g of hexadecyltrimethylammonium bromide in 150 mL of ethanol aqueous solution, adding 4.3 g of triethanolamine to the ethanol aqueous solution, and stirring at 340 rpm for 24 min to obtain a mixed solution B;

[0135] Step II, heating the mixed solution B to 86°C, adding 6.7 g of tetraethoxysilane at 410 rpm and refluxing at 86°C for 2.5 h, and obtaining a preformed product by centrifugation after the reaction is completed;

[0136] Step III, the preformed product was added to 200 mL of hydrochloric acid / ethanol solution, ultrasonically treated for 4.9 h to remove the unreacted solvent and form a hollow structure, and finally centrifugally washed three times with ethanol and deionized water, and freeze-dried for 11.1 h to obtain hollow mesoporous silica.

[0137] (2) Step S1, 0.7 g of graphene oxide was dispersed in 200 g of deionized water, and ultrasonically stirred at 330 rpm for 48 min to obtain a suspension, 5.5 g of hydrazine hydrate solution was added to the suspension, and the suspension was reacted at 73° C. for 13.3 h, and stirred at 330 rpm. After the reaction, the suspension was washed and centrifuged, and freeze-dried for 10.7 h to obtain reduced graphene oxide powder;

[0138] Step S2, immersing 0.69 g of reduced graphene oxide powder in 28 g of paraffin wax and maintaining the mixture at 87° C. for 37 min under vacuum, cooling the mixture to room temperature after the reaction is completed and removing the paraffin wax on the surface of the reduced graphene oxide powder to obtain reduced graphene oxide powder / paraffin wax;

[0139] Step S3, 2.4 g of reduced graphene oxide powder / paraffin, 19 g of deionized water, 6.4 g of hollow mesoporous silica and 7.3 g of polyvinyl alcohol are added to 68 g of epoxy resin in sequence, and stirred at 420 rpm, and then 9.1 g of polyvinyl pyrrolidone is added, and the mixture is mixed and stirred at 420 rpm for 52 min to obtain a mixed solution A;

[0140] Step S4, pouring the mixed solution A into a mold, and drying it at 61° C. in a vacuum oven for 5.8 h to obtain a high thermal conductivity graphene composite material for heat dissipation of VR equipment.

[0141] Example 8

[0142] This embodiment provides a method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment, such as Figure 1 As shown, the preparation method specifically comprises the following steps:

[0143] (1) Step I, dissolving 2.8 g of hexadecyltrimethylammonium bromide in 150 mL of ethanol aqueous solution, adding 4.6 g of triethanolamine to the ethanol aqueous solution, and stirring at 320 rpm for 27 min to obtain a mixed solution B;

[0144] Step II, heating the mixed solution B to 82°C, adding 7.4 g of tetraethoxysilane at 410 rpm and refluxing at 83°C for 2.3 h, and obtaining a preformed product by centrifugation after the reaction is completed;

[0145] Step III, the preformed product was added to 200 mL of hydrochloric acid / ethanol solution, ultrasonically treated for 5.3 h to remove the unreacted solvent and form a hollow structure, and finally centrifuged and washed three times with ethanol and deionized water, and freeze-dried for 10.7 h to obtain hollow mesoporous silica.

[0146] (2) Step S1, 1.2 g of graphene oxide was dispersed in 200 g of deionized water, and ultrasonically stirred at 320 rpm for 41 min to obtain a suspension, 4.9 g of hydrazine hydrate solution was added to the suspension, and the suspension was reacted at 70° C. for 12.5 h, and stirred at 320 rpm. After the reaction, the suspension was washed and centrifuged, and freeze-dried for 11.4 h to obtain reduced graphene oxide powder;

[0147] Step S2, immersing 0.83 g of reduced graphene oxide powder in 22 g of paraffin wax and maintaining the mixture at 83° C. for 32 min under vacuum, cooling the mixture to room temperature after the reaction is completed and removing the paraffin wax on the surface of the reduced graphene oxide powder to obtain reduced graphene oxide powder / paraffin wax;

[0148] Step S3, 2.1 g of reduced graphene oxide powder / paraffin, 17.5 g of deionized water, 5.7 g of hollow mesoporous silica and 6.1 g of polyvinyl alcohol are added to 63 g of epoxy resin in sequence, and stirred at 380 rpm, and then 6.4 g of polyvinyl pyrrolidone is added, and the mixture is mixed and stirred at 380 rpm for 46 min to obtain a mixed solution A;

[0149] Step S4, pouring the mixed solution A into a mold, and drying it at 63° C. in a vacuum oven for 4.6 h to obtain a high thermal conductivity graphene composite material for heat dissipation of VR equipment.

[0150] Comparative Example 1

[0151] This comparative example provides a high thermal conductivity graphene composite material for heat dissipation of VR equipment. The difference between it and Example 1 is that the weight of the hollow mesoporous silica is adjusted to 9.3g. Compared with Example 1, in this comparative example, the weight of the hollow mesoporous silica is increased by 3g, and the increased 3g is deducted from the reduced graphene oxide powder / paraffin, hydrazine hydrate solution, polyvinyl alcohol, epoxy resin, polyvinyl pyrrolidone and deionized water in equal proportions, so that the weight ratios of other components except the hollow mesoporous silica remain unchanged, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0152] Comparative Example 2

[0153] This comparative example provides a high thermal conductivity graphene composite material for heat dissipation of VR equipment. The difference between it and Example 1 is that the weight of the hollow mesoporous silica is adjusted to 3.3 g. Compared with Example 1, in this comparative example, the weight of the hollow mesoporous silica is reduced by 3 g, and the reduced 3 g is added in equal proportion to the weight of reduced graphene oxide powder / paraffin, hydrazine hydrate solution, polyvinyl alcohol, epoxy resin, polyvinyl pyrrolidone and deionized water, so that the weight ratios of other components except the hollow mesoporous silica remain unchanged, and other process parameters and operating steps are exactly the same as those in Example 1.

[0154] Comparative Example 3

[0155] This comparative example provides a high thermal conductivity graphene composite material for heat dissipation of VR equipment. The difference between the comparative example and Example 1 is that the weight of the reduced graphene oxide powder / paraffin is adjusted to 3.6 g. Compared with Example 1, the weight of the reduced graphene oxide powder / paraffin in this comparative example is increased by 1 g, and the increased 1 g is deducted from the weight of the hollow mesoporous silica, hydrazine hydrate solution, polyvinyl alcohol, epoxy resin, polyvinyl pyrrolidone and deionized water in proportion, so that the weight ratio of the other components except the reduced graphene oxide powder / paraffin remains unchanged, and the other process parameters and operating steps are exactly the same as those in Example 1.

[0156] Comparative Example 4

[0157] This comparative example provides a high thermal conductivity graphene composite material for heat dissipation of VR equipment, which differs from Example 1 in that the weight of reduced graphene oxide powder / paraffin is adjusted to 1.6 g. Compared with Example 1, the weight of reduced graphene oxide powder / paraffin in this comparative example is reduced by 1 g, and the reduced 1 g is added in equal proportion to the weight of hollow mesoporous silica, hydrazine hydrate solution, polyvinyl alcohol, epoxy resin, polyvinyl pyrrolidone and deionized water, so that the weight ratio of other components except reduced graphene oxide powder / paraffin remains unchanged, and other process parameters and operating steps are exactly the same as those in Example 1.

[0158] According to the national standard GB / T 29313-2012, the thermal conductivity of the high thermal conductivity graphene composite materials for heat dissipation of VR devices prepared in Examples 1 to 8 and Comparative Examples 1 to 4 was tested.

[0159] The tensile properties of high thermal conductivity graphene composite materials used for heat dissipation of VR devices were tested using an electronic tensile tester. The experimental specimens were cut to 5mm×50mm in size, the tensile speed was set to 0.5mm / s, and 3 specimens were selected for each sample for tensile testing.

[0160] According to the national standard GB / T 3356-2014, the bending strength test of the high thermal conductivity graphene composite materials for heat dissipation of VR devices prepared in Examples 1 to 8 and Comparative Examples 1 to 4 was performed, and Table 1 was obtained.

[0161] Table 1 Test results of thermal conductivity, tensile strength and bending strength of high thermal conductivity graphene composite materials for heat dissipation of VR equipment in Examples 1 to 8 and Comparative Examples 1 to 4

[0162]

[0163] It can be seen from the test data of Example 1, Comparative Example 1 and Comparative Example 2 that the thermal conductivity of Comparative Example 1 and Comparative Example 2 is lower than that of Example 1. This is because the weight of the hollow mesoporous silica in Comparative Example 1 is relatively high, and the thermal conductivity of the hollow mesoporous silica itself is relatively low. When its content is too high, it will dilute the overall thermal conductivity of the composite material, resulting in a decrease in the overall heat dissipation performance of the material. In Comparative Example 2, the weight of the hollow mesoporous silica is relatively low, and the porous structure of the hollow mesoporous silica can adsorb and fix paraffin. If the weight is relatively low, phase change materials such as paraffin may not be effectively fixed, and the heat storage and heat release capacity of the composite material may be reduced.

[0164] It can be seen from the test data of Example 1, Comparative Example 3 and Comparative Example 4 that the thermal conductivity, tensile strength and bending strength of Comparative Example 3 and Comparative Example 4 are all lower than those of Example 1. This is because the paraffin material is soft and has a low thermal conductivity. The excessive amount of reduced graphene oxide powder / paraffin in Comparative Example 3 will reduce the rigidity of the overall composite material and reduce the mechanical strength. A large amount of paraffin will dilute the thermal conductivity, resulting in a decrease in the heat dissipation performance of the material. In Comparative Example 4, paraffin is used as a phase change material. If too little reduced graphene oxide powder / paraffin is added, the heat storage capacity of the material will be weakened. Reduced graphene oxide not only improves the thermal conductivity of the material, but also enhances the mechanical strength and structural stability of the material. If too little is added, the skeleton effect of the composite material is not obvious, resulting in a decrease in the overall performance of the material.

[0165] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment, characterized in that: The preparation method comprises: Step S1, dispersing 0.5-1.3 parts by weight of graphene oxide in 200 parts by weight of deionized water, stirring and ultrasonicating at a first stirring speed to obtain a suspension, adding 3-6 parts by weight of a hydrazine hydrate solution to the suspension, reacting at a first temperature, and stirring at a first stirring speed, washing and centrifuging after the reaction is completed, and freeze-drying to obtain reduced graphene oxide powder; Step S2, immersing 0.5-1 parts by weight of reduced graphene oxide powder in 20-30 parts by weight of paraffin wax and maintaining the mixture at a second temperature under a vacuum state, cooling the mixture to room temperature after the reaction is completed and removing the paraffin wax on the surface of the reduced graphene oxide powder to obtain reduced graphene oxide powder / paraffin wax; Step S3, 2-3 parts by weight of reduced graphene oxide powder / paraffin, 15-20 parts by weight of deionized water, 5-7 parts by weight of hollow mesoporous silica and 5-8 parts by weight of polyvinyl alcohol are sequentially added to 60-70 parts by weight of epoxy resin, and stirred at a second stirring speed, and then 5-10 parts by weight of polyvinyl pyrrolidone are added, and mixed at a second stirring speed to obtain a mixed solution A; Step S4, pouring the mixed solution A into a mold, and vacuum drying it to obtain a high thermal conductivity graphene composite material for heat dissipation of VR equipment.

2. The method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment according to claim 1, characterized in that: In step S1: The first stirring speed is 300-400 rpm, the ultrasonic time is 30-50 min, the mass fraction of the hydrazine hydrate solution is 10 wt.%, the first temperature is 65-75° C., the reaction time is 12-14 h, and the freeze-drying time is 10-12 h.

3. The method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment according to claim 1, characterized in that: In step S2, the second temperature is 80-90°C, and the immersion time is 30-40 minutes.

4. The method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment according to claim 1, characterized in that: In step S3, the second stirring speed is 350-450 rpm, and the stirring time is 40-60 min.

5. The method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment according to claim 1, characterized in that: In step S4, the drying temperature is 55-65° C. and the drying time is 4-6 hours.

6. The method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment according to claim 1, characterized in that: The hollow mesoporous silica preparation method comprises: Step I, dissolving 2-3 parts by weight of hexadecyltrimethylammonium bromide in an ethanol aqueous solution, then adding 4-5 parts by weight of triethanolamine to the ethanol aqueous solution, and stirring and dissolving at a third speed to obtain a mixed solution B; Step II, heating the mixed solution B to a third temperature, adding 6-8 parts by weight of tetraethoxysilane at a fourth stirring speed and refluxing at the third temperature, and obtaining a preformed product by centrifugation after the reaction is completed; Step III, adding the preformed product into a hydrochloric acid / ethanol solution, ultrasonically treating to remove the unreacted solvent and forming a hollow structure, and finally washing by centrifugation with ethanol and deionized water three times, and freeze-drying to obtain hollow mesoporous silica.

7. The method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment according to claim 6, characterized in that: In step Ⅰ: The ethanol aqueous solution is 150 mL, the volume ratio of ethanol to deionized water is 1:2, the third stirring speed is 300-400 rpm, and the stirring time at the third speed is 20-30 min.

8. The method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment according to claim 6, characterized in that: In step II, the third temperature is 80-90° C., the fourth stirring speed is 350-450 rpm, and the reflux time is 2-3 h.

9. The method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment according to claim 6, characterized in that: In step III: The hydrochloric acid / ethanol solution is 200 mL, and the hydrochloric acid / ethanol solution includes hydrochloric acid solution and anhydrous ethanol. The mass fraction of hydrochloric acid in the hydrochloric acid solution is 37wt.%, the hydrochloric acid solution is 30 mL, the anhydrous ethanol is 170 mL, the ultrasonic power of the ultrasonic treatment is 500-800 W, the ultrasonic time is 4-6 h, and the drying time is 10-12 h.

10. A high thermal conductivity graphene composite material for heat dissipation of VR equipment prepared by the method for preparing a high thermal conductivity graphene composite material for heat dissipation of VR equipment as described in any one of claims 1 to 9.